Securitização - Coelho, Livia Alves Visnevski Fróes (2007)
The intention of this study is to carry out an analysis of securitization in Brazil and, therefore, it will present an analysis of the securitization terminology and appearance, first in the United States of America and then in Brazil. Thereafter, the legal nature and the concept of securitization will be studied pursuant to the Brazilian legislation, after which we will verify its legal structure, including (i) the incorporation of a specific purpose vehicle, consisting of an investment fund or a special purpose company, the latter usually incorporated as a joint-stock company, (ii) the assignment of credits from the company which originates the assets to the specific purpose vehicle, at which point the issue regarding the effective segregation of the applicable specific purpose vehicle s assets from the originator s assets will be analyzed, and (iii) the issuance of asset backed securities. The roles and responsibilities of the other agents which are part of the securitization process will be verified: the institution providing the structure of the operation, the fiduciary agent, the independent auditor and the rating agency. Finally, the specific securitization structures and regulations in Brazil will be described, as follows: export securitization, real estate securitization, financial credit securitization and receivables securitization in general